Building the Links Between Funding and Quality in Higher Education India's Challenge - Daugherty, Lindsay (RAND Corporation, 2013)
India has joined a worldwide trend in which nations are seeking to improve the quality of their higher education systems by giving greater autonomy and accountability to higher education institutions. In this report, the authors review India's and other countries' higher education systems and suggest seven policy actions that the Indian national government and other stakeholders can take to improve higher education by linking funding to quality.